Iterative Clipping Filtering and Saleh Model Predistorter on a MIMO-OFDM System Testbed Using Software Defined Radio - M Wisnu Gunawan; I Gede Puja Astawa; Amang Sudarsono (Advances in Technology Innovation, 2025)
The purpose of this study is to address the challenges of high peak-to-average power ratio (PAPR) and nonlinear power amplifier (PA) distortion in multiple-input multiple-output orthogonal frequency division multiplexing (MIMO-OFDM) systems based on the IEEE 802.11ac. The research integrates iterative clipping filtering (ICF) for PAPR reduction and the Saleh model predistortion (PD) for PA linearization. Implemented on a software defined radio (SDR) platform using NI-USRP devices, the system is evaluated in real-world line-of-sight (LOS) and non-line-of-sight (NLOS) environments. Results show significant PAPR reduction, from 19.7 dB to 10.3 dB, and improved PA linearity, achieving a 94.80% error vector magnitude (EVM) reduction. Furthermore, the combined approach exhibits lower symbol error rates (SER) and error-free data transmission, particularly under LOS conditions. Compared to conventional methods, the system demonstrates superior execution efficiency with 475–503 ms processing times.